Rare bird documentation form for Greater Scaup at Saylorville Lake, 1988 - Thomas, Michael K.et al (1988)
Rare bird documentation form for two Greater Scaups at Saylorville Lake in Polk County, IA on November 20, 1988. Epson - sheet feed